THE WORLD LEADERS THROUGH THE PRISM OF INFORMATION POLICY DURING THE COVID-19 PANDEMIC - Младьонова, О. Д. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The article considers the information policy in the current global crisis, weighed down by the pandemic of the COVID-19, which has sunk many countries around the world. In the setting of extreme conditions, the behaviour, rhetoric, slogans of world leaders and methods of mass communication are investigated. It is noted that the response of a certain number of world leaders was not always based on objective and rational recommendations of experts; moreover, they were even indicated by the absence of any scientific justification. It is proposed to classify the behaviour of world leaders during the fight against a pandemic according to the following four types: «Silence of the Lambs», «Riot of the Elites», «Tough Rejection», «Pendulum». The following types of approaches in internal communications (from the leader to people) are distinguished during the SARS-CoV-2 coronavirus epidemic, due to the tasks facing politicians and their vision of solving the problem: «Caring father», «Populist», «Tough leader», and «Tactician», depending on the internal socio-political situation in the country and the international situation, as well as on the personality traits of the leader himself, taking into account the predicted reaction of the neighbouring countries and the international community. Relevant examples of political leaders of each of these types are given. It is emphasized that world leaders did not take advantage of the emergency and did not formulate a concept for the future of their countries, confining themselves to general phrases. The forecasted trends are the demand for certain types of political leader after the pandemic, the need for the development of mass ideology, new events and guarantees of protection.